The Role of Semiotic Metaphor in the Verbal-Visual Interplay of Three Children’s Picture Books. A Multisemiotic Systemic-Functional Approach - Moya Guijarro, Arsenio Jesús (Atlantis. Journal of the Spanish Association for Anglo-American Studies, 2016)
This paper aims to explore how the use of semiotic metaphors in picture books contributes to children’s understanding of the stories. The three picture books selected for analysis were written during the twentieth century and respond to a standard of literary quality: Guess How Much I Love You (1994), Where the Wild Things Are (1963) and Gorilla (1983). The concept of semiotic metaphor as a tool to create ideational meaning is analysed within the framework of Systemic Functional Linguistics and Systemic-Functional Multimodal Discourse Analysis. Kay O’Halloran extends the Hallidayan concept of grammatical metaphor to the semiotic metaphor in order to determine how verbal and visual modes interact with each other in multimodal texts. Like grammatical metaphor, semiotic metaphor also involves a shift in the grammatical class or function of an element. As this process does not take place intra-semiotically, but rather inter-semiotically, the reconstrual produces a semantic change in the function of that element, creating a new way of making meaning and representing reality. The results of the analysis show that semiotic metaphors are essentially used in children’s tales to facilitate young children’s understanding of the story by making some abstract phenomena related to states of being more concrete and specific. Keywords: Systemic Functional Linguistics; grammatical metaphor; semiotic metaphor; verbal-visual intersemiosis; picture books